Computational Methods and Fast Algorithms for Boltzmann Equations - Pareschi, L. (Lecture Notes On The Discretization Of The Boltzmann Equation, 2003)
The following sections are included: Introduction A one-dimensional example The Boltzmann equation with inelastic collisions Splitting algorithms spectral method Fast algorithms Numerical examples The multi-dimensional case The Boltmann equation for rarefied gases A spectral method Properties of the spectral method Accelerated algorithms Numerical tests References